2007
DOI: 10.1080/02786820701408517
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Dust Capture and Induced Airflow of Various Spray Nozzle Designs

Abstract: Water spray characteristics, including droplet size and velocity, airborne dust capture potential, and induced airflow quantity for various spray nozzle designs were evaluated to provide basic information for improving spray applications. Water droplet size and velocity characteristics were initially measured by a Phase Doppler Particle Analyzer (PDPA) for hollow cone, full cone, flat fan, and air atomized spray nozzles at similar operating parameters. Airflow inducement and dust capture experiments were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…Six of the included sprays had been tested previously by Pollock and Organiscak (2007) for respirable dust capture efficiency, airflow inducement and various spray droplet characteristics. Gemci et al (2003) had measured the water droplet Sauter mean diameter (SMD) and mean velocity, V , for these same sprays using a Phase Doppler Particle Analyzer at two distances along the nozzle axis under the same operating parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of the included sprays had been tested previously by Pollock and Organiscak (2007) for respirable dust capture efficiency, airflow inducement and various spray droplet characteristics. Gemci et al (2003) had measured the water droplet Sauter mean diameter (SMD) and mean velocity, V , for these same sprays using a Phase Doppler Particle Analyzer at two distances along the nozzle axis under the same operating parameters.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Kost, duBreuil and Saltsman (1979) found that, independent of spray type selected, sprays oriented downstream in a 0.5-m/s (100-fpm) tunnel were 20 to 30 percent more effective at controlling airborne dust than those oriented upstream. More recent investigations by NIOSH examined spray airflow inducement and its effect on respirable dust capture potential (Pollock and Organiscak, 2007). This effort found that open-air, or unconfined, sprays with high airflow inducement did not necessarily result in higher rates of airborne dust capture, though higher pressures globally produced higher droplet velocities and improved capture efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the dust control measures available, field practice has demonstrated that the control of respirable dust in longwall faces is very difficult and often ineffective [13][14]. This is particularly true in the Shihe colliery, where the dust concentration, particularly respirable dust, at its high longwall faces often exceeds the maximum allowable dust limit.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers more simply related several empirical spray operating parameters to airborne dust capture. Common spray operating parameters studied include spray operating pressure, water flow rate, water flow to airflow ratio and spray power to airflow ratio (Jayaraman, 1982; Jones and James, 1987; Organiscak and Pollock, 2007; Pollock and Organiscak, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Spray nozzle parameters such as orifice diameter are directly related to water quantity at constant pressure, while discharge angle is indirectly related to droplet size and velocity at constant pressure (Streeter and Wylie, 1979; Pollock and Organiscak, 2007; Klima et al, 2017). Water spray operating pressure is indirectly related to water droplet size and directly related to water droplet velocity for a particular spray nozzle (Cheng.…”
Section: Introductionmentioning
confidence: 99%